Extracellular Acidification Inhibits the ROS-Dependent Formation of Neutrophil Extracellular Traps - Behnen, Martina; Möller, Sonja; Brozek, Antonia; Klinger, Matthias; Laskay, Tamás (Frontiers in Immunology, 2017)
1. Introduction The inflammatory microenvironment is commonly characterized by extracellular acidosis (pH <7.35). Sensitivity to pH, CO2 or bicarbonate concentrations allows neutrophils to react to changes in their environment and to detect inflamed areas in the tissue. One important antimicrobial effector mechanism is the production of neutrophil extracellular traps (NETs), which are released during a programmed ROS-dependent cell death, the so called NETosis. Although several functions of neutrophils have been analyzed under acidic conditions, the effect of extracellular acidosis on NETosis remains mainly unexplored and the available experimental results are contradictory. We performed a comprehensive study with the aim to elucidate the effect of extracellular acidosis on ROS-dependent NETosis of primary human neutrophils and to identify the underlying mechanisms. The study was performed in parallel in a CO2-bicabonate buffered culture medium which mimics in vivo conditions, and under HEPES buffered conditions to verify the effect of pH independent of CO2 or bicarbonate. We could clearly show that extracellular acidosis (pH 6.5, 6.0 and 5.5) and intracellular acidification inhibit the release of ROS-dependent NETs upon stimulation of neutrophils with PMA and immobilized immune complexes. Moreover, our findings suggest that the diminished NET release is a consequence of reduced ROS production and diminished glycolysis of neutrophils under acidic conditions. It was suggested previously, that neutrophils can sense the border of inflamed tissue by the pH gradient and that a drop in pH serves as an indicator for the progress of inflammation. Following this hypothesis our data indicate that an acidic inflammatory environment results in inhibition of extracellular operating effector mechanisms of neutrophils such as release of ROS and NETs. This way the release of toxic components and tissue damage can be avoided. However, we observed that major antimicrobial effector mechanisms such as phagocytosis and the killing of pathogens by neutrophils remain functional under acidic conditions.